2012
DOI: 10.1096/fj.12-213595
|View full text |Cite
|
Sign up to set email alerts
|

Ferritin is the key to dietary iron absorption and tissue iron detoxification inDrosophila melanogaster

Abstract: Mammalian ferritin is predominantly in the cytosol, with a minor portion found in plasma. In most insects, including Drosophila melanogaster, ferritin belongs to the secretory type. The functional role of secretory ferritin in iron homeostasis remains poorly understood in insects as well as in mammalians. Here we used Drosophila to dissect the involvement of ferritin in insect iron metabolism. Midgut-specific knockdown of ferritin resulted in iron accumulation in the gut but systemic iron deficiency (37% contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
126
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 93 publications
(148 citation statements)
references
References 44 publications
11
126
2
Order By: Relevance
“…Evidences suggested that the origin of serum ferritin must indeed largely, if not entirely, be seen as cellular damage, that is to say it is mainly a leakage product from damaged cells. Ferritin is genuinely secreted, as it is for instance in insects [41][42][43], and mammalian does not have suitable leader (secretion signal) sequences for ferritin secretion. There is no any actual evidence for regulated or active secretion of ferritin in humans in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Evidences suggested that the origin of serum ferritin must indeed largely, if not entirely, be seen as cellular damage, that is to say it is mainly a leakage product from damaged cells. Ferritin is genuinely secreted, as it is for instance in insects [41][42][43], and mammalian does not have suitable leader (secretion signal) sequences for ferritin secretion. There is no any actual evidence for regulated or active secretion of ferritin in humans in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Iron uptake is, in part, mediated by the divalent transporter ion transporter 1 (DMT1) homolog Malvolio (11). In addition to their role in iron storage, ferritins also mediate iron export from the midgut to the hemolymph (107,181). Finally, zinc absorption is mediated by ZIP transporters, whereas zinc efflux from the cytoplasm to the hemolymph is mediated by ZnT transporters.…”
Section: Incorporation Of Metalsmentioning
confidence: 99%
“…Fer1HCH and Fer2LCH coassemble to holoferritin to store iron [26]. However, in contrast to mammals, fly ferritin localizes to the endoplasmic reticulum and the Golgi complex and it is secreted to the hemolymph for iron sequestration/transport [26,27]. Fer3HCH is the ortholog to mammalian mitochondrial ferritin [28].…”
Section: Introductionmentioning
confidence: 99%